Good Corporate Governance And The Impact On Earnings Management Actions - Denny Putri Hapsari; Herman Wijaya; Nana Umdiana (Jurnal Riset Akuntansi Terpadu, 2022)
This research aimed to examine the effect of managerial ownership, independent commissioners, and audit committees which are proxies of Good Corporate Governance (GCG), and their effect on earnings management in the population of companies listed on the IDX with a research sample of 11 companies for the 2015 – 2019 periods. From the results of purposive sampling, 55 samples of data were obtained from basic and chemical industrial manufacturing companies. Quantitative methods were used in this study. Data analysis was performed by using SPSS software with multiple Linear Regression analyses where managerial ownership and the Audit Committee do not affect Earnings Management practice. However, the composition of the Independent Board of Commissioners has a significant negative effect on Earnings Management.